Condensed‐Phase, Halogen‐Bonded CF3I and C2F5I Adducts for Perfluoroalkylation Reactions1. (30th January 2015) - Sladojevich, Filippo; McNeill, Eric; Börgel, Jonas; Zheng, Shao‐Liang; Ritter, Tobias
Abstract: A family of practical, liquid trifluoromethylation and pentafluoroethylation reagents is described. We show how halogen bonding can be used to obtain easily handled liquid reagents from gaseous CF3 I and CF3 CF2 I. The synthetic utility of the new reagents is exemplified by a novel direct arene trifluoromethylation reaction as well as adaptations of other perfluoroalkylation reactions.